Development of a relative coastal vulnerability index in a macro-tidal environment for climate change adaptation - Tibbetts, Jeremy R.; van Proosdij, Danika (Journal of coastal conservation, 2013)
Coastal vulnerability assessments to climate change impacts have been conducted in the past. However, few if any account for the highly variable risk associated with tidal stage in macro-tidal environments. The purpose of this research was to develop a geomatics tool which interactively determines the biophysical vulnerability of a macro-tidal estuary in the Bay of Fundy to varying levels of storm surge and tide state. A conceptual framework was designed to illustrate the relative interrelationships between exposure conditions (surge height, tidal stage), biophysical state (freeboard, exposure, width of foreshore, intertidal slope, observed erodibility, shore protection) and morphological resilience condition. This conceptual framework was then used to develop a dynamic, custom Python programming script within ArcGIS 9.3 to calculate coastal vulnerability for user determined combinations of surge height and tide state. The analysis was conducted for four coastlines, backshore, upper foreshore, middle foreshore and lower foreshore, to reflect varying biophysical states with varying tide levels. The results of the tool were compared with known areas of concern (high erosion, dyke overtopping), as determined by historical records, local expert knowledge and GIS analysis of aerial photography. The number of known locations of concern is lower than that of the results produced by the tool. This is most likely due to the results being analyzed at extreme water levels, greater than higher high water large tide. However, this estimation of vulnerability may limit negative impacts of climate change by highlighting vulnerable areas prior to an event, allowing coastal managers and planners to install measures to reduce the vulnerability and enhance the adaptive capacity of local communities.